KETIDAKADILAN GENDER DALAM PENGUPAHAN PEKERJA PEREMPUAN PADA SEKTOR PERTANIAN: STUDI KASUS DI KENAGARIAN BATU PALANO, KECAMATAN SUNGAI PUA - Sari Nurmala, Mutia Kahanna (LP2M Universitas Muslim Nusantara Al Washliyah, 2026)
This study examines gender inequality in the wage system of female agricultural workers in Kenagarian Batu Palano, Sungai Pua District. The aim of the study is to identify the factors causing gender-based wage disparities among agricultural workers and to analyze the economic impacts of wage inequality on agricultural workers in Kenagarian Batu Palano. The theoretical framework used in this research is the gender injustice theory proposed by Mansour Fakih. This study employs a qualitative method using observation, interviews, and documentation, involving female agricultural workers, male agricultural workers, landowners, nagari government officials, and community leaders. The findings show that female workers receive lower wages than male workers despite performing the same tasks, working hours, and responsibilities, with female workers earning Rp 80,000 per day and male workers earning Rp 120,000 per day. The forms of gender injustice experienced by female agricultural workers in Kenagarian Batu Palano include subordination, marginalization, stereotyping, double burden, and non-physical violence. The factors contributing to wage inequality are long-standing traditions, gender stereotypes held by landowners, and the absence of written regulations regarding wage determination. Furthermore, the economic impacts of wage inequality include limited ability to meet daily needs, inability to save and invest, and restricted access to children’s education.